Acoustics of a traditional dwelling and music of Jordan - Alshurman, Ali Salem; Qaqish , RaEd (project baikal, 2023)
The ancient culture of Jordan developed against the background of a peculiar climate and landscape, which determined the features of the traditional Jordanian dwelling. The design of the house and the choice of materials reveal a connection with the musical traditions of Jordan. The musical genre of folk song-story and the sound of folk musical instruments are supported by the sound–absorbing properties of traditional building materials – felt, woolen fabrics, adobe. The cave dwelling, also typical of Jordan, has not been studied enough from the point of view of acoustics.
Keywords: architecture; acoustics; music; dwelling; traditions